Drawing Graphs with GLEE - Nachmanson, Lev; Robertson, George; Lee, Bongshin (2007)
This paper describes novel methods we developed to lay out graphs using Sugiyama's scheme in a tool named GLEE. The main contributions are: a heuristic for creating a graph layout with a given aspect ratio, an efficient method of edge-crossings counting while performing adjacent vertex swaps, and a simple and fast spline routing algorithm.
Graph Drawing 2007